Application of elevated pressure in the fixative solution for preservation of tissue morphology and its comparison with conventional fixation method. (September 2014) - Agrawal, Tripti; Bhandari, Saurabh
<x content-type="archive" xml:space="preserve">Abstract</x> Fixation is first step toward preservation and analysis of the tissue. Fixation is influenced by many physical and chemical factors but the influence of elevated pressure has not been studied. The aim of the present study is to analyze the effect of elevated pressure to preserve tissue morphology. A sample size of 60 tissues was taken and the tissues were fixed by two different methods. The group fixed by elevated pressure had a higher coefficient of penetration and less fixation artifacts. Fixation using increased hydraulic pressure had shown positive correlation with the fixation efficiency of tissue.